Pretreatment With Risperidone Ameliorates Systemic LPS-Induced Oxidative Stress in the Cortex and Hippocampus - Al-Amin, Md. Mamun; Choudhury, Md. Faiyad Rahman; Chowdhury, Al Saad; Chowdhury, Tahsinur Rahman; Jain, Preeti; Kazi, Mohsin; Alkholief, Musaed; Alshehri, Sultan M.; Reza, Hasan Mahmud (Frontiers in Neuroscience, 2018)
Risperidone (RIS), an atypical antipsychotic has been found to show anti-inflammatory effect against lipopolysaccharide (LPS)-induced inflammation. In vitro study has revealed that RIS inhibits the LPS-induced reactive oxygen species (ROS) formation. We investigated the antioxidant effects of RIS on LPS-induced oxidative stress markers in Swiss albino mice. Ten weeks old male Swiss albino mice (30 ± 2 g) were pretreated with either distilled water (control) or RIS (3 mg/kg) for 7 days. On day 8, animals were challenged with a single dose of LPS (0.8 mg/kg) while control animals received distilled water only. The animals were sacrificed after 24 h of LPS administration and tissue samples were collected. RIS administration significantly (p < 0.05) reduced the LPS-induced elevated levels of lipid peroxidation product malondialdehyde (MDA), advanced protein oxidation products, and nitric oxide (NO) in the cortex. Catalase (CAT) and superoxide dismutase (SOD) levels were also diminished while the level of glutathione (GSH) was enhanced. Hippocampus data showed that RIS significantly (p < 0.05) reduced the LPS-induced increased levels of MDA and NO, and SOD activity. Our results suggest that LPS-induced neuronal oxidative damage can be alleviated by the pretreatment with RIS and the effect is shown presumably by scavenging of the ROS by risperidone as an antioxidant.